Pengembangan LKPD HOTS Bernuansa Sikap Tanggung Jawab Materi Pecahan Kelas V SDN 12 Pontianak Kota - Ria Firsta Mutiara; Bistari Bistari; Siti Halidjah (AS-SABIQUN, 2023)
This study aims to produce a HOTS Student Worksheet design with a nuanced attitude of responsibility in the material for adding and subtracting fractions for class V SDN 12 Pontianak Kota. The research method used is research and development (RnD) by adapting the Thiagarajan 4D development model (define, design, development and dissemination). The data source for this research is the results of the validation of the three validators and the results of the student worksheet trials. The data collection technique for this research was a validator validation questionnaire, test questions for students, as well as documentation on the LKPD used by the teacher. The results of the research show that during the process of developing HOTS LKPD with a nuanced attitude of responsibility it is carried out only in three stages, namely the define, design and development stages. The percentage of LKPD validity criteria from the material aspect has an average of 4 with very valid criteria, from the language aspect it is 4 with very valid criteria, from the display aspect it is 3.86 with very valid criteria, and from the aspect of conformity with the responsibility indicator it is 4 with very valid criteria. The percentage of the criteria for the completeness level of students' scores in the first trial obtained a completeness percentage of 100% with very high criteria and the second trial obtained a completeness percentage of 73% with high criteria.